Treatment outcomes and prognosis of immune checkpoint inhibitors therapy in patients with advanced thymic carcinoma: A multicentre retrospective study. (October 2022) - Wang, Wenxian; Lin, Gen; Hao, Yue; Guan, Yelan; Zhang, Yuxin; Xu, Chunwei; Wang, Qian; Wang, Dong; Jiang, Zhansheng; Cai, Jing; Lou, Guangyuan; Song, Zhengbo; et al.
Abstract: Background: Immunotherapy has demonstrated good efficacy and survival outcomes in solid tumours. However, efficacy data for immune checkpoint inhibitors (ICIs) in advanced thymic carcinoma are lacking. The present study aimed to assess the activity of ICIs in advanced thymic carcinoma. Methods: A multicentre retrospective study was conducted to explore the efficacy and safety of ICIs for advanced thymic carcinoma. Objective response rate (ORR), progression-free survival (PFS), overall survival, and immune-related adverse events (irAEs) were analysed. In addition, factors independently associated with treatment efficacy and survival outcomes were evaluated. Results: A total of 77 patients with advanced thymic carcinoma were enrolled between March 2016 and September 2021. The ORR was existing the difference between ICIs monotherapy (n = 23) and ICIs combined with chemotherapy (n = 54) (17.4% versus 44.4%, P = 0.024). The ICIs combination treatments were associated with better median PFS (mPFS) compared to ICIs monotherapy (12.7 months versus 2.1 months, P < 0.001). Notably, liver or brain metastasis was a poor prognostic factor of mPFS (1.8 months versus 3.5 months, P = 0.012) in the ICIs monotherapy group. In addition, mPFS for the first-line treatment (n = 27) was longer than that for ICIs as the second- or posterior-line treatment (n = 50) (P < 0.001). The incidence of irAEs was 54.5% (42/77) in the 77 enrolled patients. The incidence of grade 3–4 irAE was 15.6% (12/77). Conclusions: Immunotherapy is effective in advanced thymic carcinoma, especially for combination with chemotherapy showed promising antitumour activity, which indicates worthy of combination treatment strategy for further study. IrAEs also require close monitoring and management. Highlights: Immunotherapy is effective in advanced thymic carcinoma. Immunochemotherapy was associated with better efficacy compared to immune checkpoint inhibitors monotherapy. Immunochemotherapy as first line treatments may be a good treatment choice. Liver or brain metastasis was a poor prognostic factor of mPFS in immune checkpoint inhibitors monotherapy.